HER2-positive metastatic breast cancer with brain metastases responds favorably to pyrotinib and trastuzumab-based treatment: A case report and literature review - Chen, Min-long; Yu, Wenjie; Cui, Binbin; Yu, Yijian; Ma, Zhaosheng (Frontiers in Oncology, 2023)
For HER2-positive metastatic breast cancer patients with brain involved at initial diagnose，there was no standard regimen before 2022 when HER2CLIMB trial published its final overall survival analysis，and the prognosis is relatively poor under current treatment strategy. We herein reported a case of a female patient, who initially diagnosed with HER2 positive metastatic breast cancer with brain metastases, receiving Pyrotinib and trastuzumab based systematic therapy after palliative craniocerebral radiotherapy as first line systematic therapy. During the treatment，the tumor lesions showed obvious regression, chemotherapy drugs were gradually removed from the regimen. The patient continued receiving trastuzumab and pyrotinib for HER2-targeted therapy. She had achieved more than 26 months of disease free survival and the disease was stable during evaluation in April 2022. Radiotherapy followed by dual HER2-targeted therapy of macromolecular monoclonal antibodies Trastuzumab and micromolecular TKI pyrotinib plus chemotherapy could be an alternative option for this subtype of patients and need to be further verified by future clinical trials.